Implications of unreliable species identification methods for Neotropical deer conservation planning - Peres, Pedro Henrique de Faria [UNESP]; Grotta-Neto, Francisco; Luduvério, Douglas Jovino [UNESP]; Oliveira, Márcio Leite de [UNESP]; Duarte, José Maurício Barbanti [UNESP] (Elsevier, 2021)
Deer species play a key role in processes that maintain ecosystem community structure and composition. However, several of the species are considered at risk of extinction. One of the strategies for their conservation is the maintenance of legally protected areas in which administration is prescribed by a management plan. Species inventories form the basis of this instrument as it allows to identify key resources and taxons. We reviewed the management plans of Brazilian protected areas to assess the suitability of methods employed to identify deer species. We reviewed 118 management plans (covering 298,000 km2 of protected area) and checked each occurrence record for information regarding detection methods, which we classified according to their suitability for species-level identification. We found that 38% of the records did not report the species detection method used. Specific identifications were obtained through seven different methodologies, of which 12% were considered suitable, 28% were suitable with caveats, and 60% were unsuitable for species identification. We conclude it is necessary to improve the scientific rigor applied to inventories and data collection to avoid producing further inconsistent information, as this might affect management actions and risks the exclusion of threatened species from public policies on conservation planning.
Keywords: Cervidae; Conservation effectiveness; Mammal inventory; Management plan; Mazama; Protected area